STRATEGI PEMULIHAN DAMPAK WABAH COVID PADA SEKTOR PARIWISATA DI DAERAH ISTIMEWA YOGYAKARTA - Pangky Arbindarta Kusuma; Dyah Mutiarin; Janianton Damanik (STIE Pariwisata API Yogyakarta, 2021)
The shocks caused by the Covid-19 pandemic had a major impact on the tourism sector and the economy. Yogyakarta is one of the main destinations for domestic and international tourism in Indonesia. Unfortunately, the tourism sector in Yogyakarta is also affected by the COVID-19 pandemic. This study aims to analyze the impact of the Covid-19 pandemic on the tourism sector and recovery strategies during and after the Covid-19 pandemic in the Special Region of Yogyakarta. This research was compiled using a descriptive qualitative methodology, data collection was carried out by studying literature and interviews with resource persons. The results showed that the growth of tourists during the pandemic period was negative, as well as the growth rate of hotel occupancy was also negative. The tourism industry perpetrators suffered huge losses and many workers were sent home without being paid until they were terminated. The recovery of the tourism sector requires a long stageand will be carried out in stages. The first phase has been started in june 2020 and is expected to move towards a new normal in 2022. Several action plans are drawn up for the recovery process. The action plan includes developing health protocols, creating digital tourism, a tourism information system, and SMART Tourism. Local governments and tourism industry players in DIY need to build SMART Tourism for sustainable tourism after the Covid-19 pandemic.SMART Tourism is an innovation in the tourism sector by utilizing information technology in integrating tourism activities.